The Effect of Early Mobilization on Functional Status of Stroke Patients: A Literature Review - Mustikaningrum, Retno Endarwati; Handayani, Fitria; Hastuti, Yuni Dwi; Latumanuwij, Romy; Fieten, Marloes (Holistic Nursing and Health Science, 2023)
Stroke impact to the altering functional status. Early mobilization is one of stroke care components that can minimize impact due to altering functional status such as weakness and paralysis in stroke patients. The review of early mobilization was proved increasing the functional status among critical illness patients. Limited review regarding the effect of early mobilization on changes in the level of functional status of stroke patients The aim the study was to determine the effect of early mobilization at the level of functional status of stroke patients. This research used the literature review with the MeSH search tool. The keywords and syntax included "stroke", "early mobilization", and "functional status". Articles found with keywords early mobilization; functional status; stroke retrieve 12,114 articles, namely 2069 articles from Proquest, 4774 articles from Pubmed, 35 articles from Scopus, and 5236 articles from ScienceDirect which were filtered based on the specified criteria and obtained 10 articles for review published in the period 2011-2021, with patient research samples strokes. The effect of early mobilization mostly showedan increasing degree of functional status level among stroke patients. It is recommended to provide early mobilization among stroke patient. Future research should conduct a meta-analysis in analysing effect of early mobilisation among stroke patients.